2011
DOI: 10.1111/j.1439-0507.2010.01994.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antifungal evaluation and structure–activity relationship of diphenyl diselenide and synthetic analogues

Abstract: We report on in vitro antifungal activity and the structure-activity relationship of diphenyl diselenide [(PhSe)(2) ] and its synthetic analogues, (p-Cl-C(6) H(4) Se)(2), (m-CF(3)-C(6) H(4)Se)(2) and (p-CH(3)O-C(6) H(4)Se)(2), against 116 strains of pathogenic fungi. (PhSe)(2) showed the highest inhibitory activity against Candida albicans (minimum inhibitory concentration of 4-32 μg ml(-1) ), Candida dubliniensis (2-16 μg ml(-1)), Aspergillus spp. (0.5-64 μg ml(-1)) and Fusarium spp. (2-16 μg ml(-1)). Its min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 12 publications
0
25
0
Order By: Relevance
“…Ebselen and diselenides have demonstrated activity against Fusarium sp. when administrated alone or in combination with other antifungal drugs showing good synergistic effects ,. It was shown that a piperidine isoselenocyanate derivative is the most active among its isosters against selected fungi, including Fusarium culmorum .…”
Section: Introductionmentioning
confidence: 99%
“…Ebselen and diselenides have demonstrated activity against Fusarium sp. when administrated alone or in combination with other antifungal drugs showing good synergistic effects ,. It was shown that a piperidine isoselenocyanate derivative is the most active among its isosters against selected fungi, including Fusarium culmorum .…”
Section: Introductionmentioning
confidence: 99%
“…In particular, organoselenium coating on cellulose was able to inhibit P. aeruginosa and S. aureus biofilm formation [ 38 , 39 ]. The antifungal property of biphelyl diselenide (PhSe) 2 against different species of Candida has been reported by Loreto ES et al [ 16 ]. The values for C. albicans reported in their study are similar to those obtained in our experimental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have demonstrated the antimicrobial activity of different organoselenium compounds [ 14 ]. Diselenides have been studied for their antimicrobial activity; diphenyl diselenide and 2,2’-dithienyl diselenide have shown antibacterial and antifungal acivities [ 15 , 16 ], moreover, selenocyanate and diselenides have been considered as a new class of antileishmanial compounds [ 17 ]. Finally, alkyl and aryl diselenides have shown microbial and antiviral activities [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Biological studies demonstrated its potential use as antimicrobial agent. In particular, it was reported its antifun-gal effects against some mycetes [4]. Compound 1b was tested in vitro and in vivo models, alone and in combination with antifungal drugs proving its inhibitory effect on the growth of Candida glabrata [5].…”
Section: Diselenides and Selenocyanatesmentioning
confidence: 99%